Evaluated anatomical variations in children by sacrococcygeal ultrasonography as a new tool: a report from a Chinese tertiary hospital - Shan Wang; Lei Hu; Xin-lu Yang; Ting-ting Yan; Chun-lin Xie; Sheng Wang; Ying Liu; Xiao-qing Chai; Ling Zhou; Wei Gao (Annals of Medicine)
Objective Anatomical variations in the sacrococcygeal region can lead to complications such as accidental dural puncture during caudal block. This study aimed to determine the prevalence of sacrococcygeal anatomical variations using ultrasonography and to evaluate the necessity of ultrasound guidance in sacral block procedures.Methods Ultrasound findings of sacrococcygeal anatomy were validated against magnetic resonance imaging (MRI). A detailed ultrasound protocol was subsequently applied to assess sacrococcygeal anatomy in pediatric patients.Results Ultrasound and MRI demonstrated strong concordance in evaluating sacrococcygeal anatomy. The most common anatomical variation was a low-lying dural sac (16.2%), followed by incomplete sacral cornua (4.9%). The dural sac termination level was inversely associated with age (odds ratio: 0.996, 95% CI: 0.945–0.987; p < 0.001). Other variations included abnormal coccyx curvature (4.3%), sacral skewness (3.8%), and sacral hiatus atresia (1.1%), with no pathological abnormalities detected.Conclusion Comprehensive ultrasound scanning effectively identifies anatomical variations in the sacrococcygeal region of pediatric patients, which are highly prevalent. Routine preprocedural ultrasound examinations and ultrasound guidance during caudal block procedures are strongly recommended to enhance safety and accuracy.